Novel Plasmonic Nanometal - Rare-Earth Ions co-doped Antimony Glasses for Nanophotonic Applications. Issue 1788 (2015) - Som, Tirtha; Karmakar, Basudeb
ABSTRACT: Glasses are recognized as the ideal hosts to incorporate plasmonic metal nanoparticles (NPs), semiconductor NPs, and luminescent rare-earth (RE 3+ ) ions. This is due to their unique optical properties, stability, absence of high energy bond vibrations and inertness towards the incorporated NPs. However, conventional methods of metal-glass nanocomposite fabrication involve ion-implantation or sputtering and subsequent heat-treatment under H2, UV-light/X-ray/γ- or laser irradiation. They are (i) multi-step, (ii) require expensive set-up, (iii) bear risk of sample damage and (iv) the formation of NPs occurs only in surface layers. Here we develop two novel glass-systems K2 O-B2 O3 -Sb2 O3 and K2 O-B2 O3 -Sb2 O3 -ZnO. Using the selective reducing property of the main component Sb2 O3 in these hosts, here we demonstrate for the first time the strategy for single-step in-situ fabrication of metal (M 0 ) NPs and RE 3+ ions co-embedded within bulk glasses. This new series of novel composites co-embedding metal NPs (elliptical Au, elongated Ag NPs and Aucore -AuAgshell NPs) and RE 3+ ions exhibit enhanced upconversion for solar panels, advanced displays and other nanophotonic applications. Metal NPs exhibit surface plasmons resonance results in concentration and enhancement of the local electromagnetic field (LFE) around them. The luminescent RE 3+ ion in the vicinity experiences the local field effect. We observe that the LFE effect is stronger on electric dipole transitions of the RE 3+ than the magnetic dipole ones. LFE induced by nano Au enhance the (i) 4 G7/2 → 4 I9/2 540 nm green and 4 G7/2 → 4 I15/2 650 nm red upconversion emissions of Nd 3+ by 9 and 11 fold, (ii) electric dipole 4 G5/2 → 6 H9/2 636 nm red upconversion of Sm 3+ by about 7 fold and (ii) 4 S3/2 → 4 I15/2 536 nm green and 4 F9/2 → 4 I15/2 645 nm red emissions of Er 3+ by 2 and 5 fold respectively. LFE induced by nano Ag enhance both the green and red upconversion emission of Er 3+ by 8 fold. The Aucore -AuAgshell NPs enhance the red upconversion of Sm 3+ only by 2 fold due to smaller LFE effect of bimetallic NPs. All the Au-doped antimony glasses are dichroic. They transmit the blue light and reflect the brown light, which make them very interesting material comparable to the historic Lycurgus Cup.